Evidence on the effectiveness of value-based payment schemes implemented in a hospital setting: A systematic review - Shahriyar Mokhtary; Ali Janati; Mahmood Yousefi; Behzad Raei (Wolters Kluwer Medknow Publications, 2024)
Value-based payment is among payment models rewarding health care providers for achieving pre-defined targets of quality or efficiency measures of care. This paper aims to identify the evidence of the effectiveness of value-based payment schemes implemented in hospital settings. A systematic review of databases for studies published from 2000 to 2022 that evaluated VBP programs was conducted. We searched four databases including PubMed, Scopus, Embase, and Web of Sciences in July 2023. Studies were screened and assessed for eligibility. A thematic analysis approach was used to synthesize and summarize the findings. Overall, 29 articles looking into the VBP programs have been included. Most articles describe the effects on the outcome of care (n = 18). The findings of a great deal of evidence in this field show that VBP is not correlated with some outcome measures including hospital-acquired conditions, 30-day mortality, mortality trends, as well as mortality among patients with acute myocardial infarction or heart failure. Only three of 12 studies have revealed a positive relationship between a P4P program and efficiency. Seven studies from the United States (US) found no evidence or mixed findings on the effects of P4P on efficiency. The magnitude of the effects of VBP on healthcare quality, patient experience, and costs has often been small and non-significant. The unintended negative impact of incentives in value-based payment on hospitals should be tackled when adopting policies and decisions.